الوثائق الليبية المودعة بالأرشيف الوطني الفرنسي ودور المركز الليبي للمحفوظات والدراسات التاريخية في جمعها وحفظها: وثائق الزاوية السنوسية ببئر علالي بتشاد المصادرة أنموذجا 1901- 1902م (مجلة جامعة سرت للعلوم الانسانية, 2024)
The historical documents confiscated by the French forces after their occupation of the Zawiya of Bir Alali in Chad at the beginning of December 1902 are of great importance. These documents were represented in a large number of important historical correspondences between the most famous leaders of the Senussi order, some of the sheikhs of the Zawiyas and the leaders of the jihad against the French occupation, some of the sultans of the neighboring Islamic kingdoms. They have been preserved in the French National Archives. Working on restoring the origin of these documents is an urgent necessity to add them to the collection of international historical documents that the Libyan Center for Archives and Historical Studies in Tripoli carried out and is still continuing its role in collecting, preserving and archiving them to be a source for academic researchers.
Keywords: Zawiya of Bir Alali ,1902; Confiscated Senussi Documents; Libya Documents in the French Archives; French-Libyan Relations; Libyan Centre for Archives